2016
DOI: 10.7860/jcdr/2016/16838.7248
|View full text |Cite
|
Sign up to set email alerts
|

A Prediction Formula for Double Product in Pregnancy

Abstract: IntrOductIOnPregnancy is the most important and essential physiological adaptation in the body. Overwhelming changes occur virtually in all the systems of the body, modifications in the cardiovascular system are constituent of the same. Systolic and diastolic blood pressures are found to decrease during second trimester. Cardiac output, heart rate and stroke volume tend to increase during pregnancy, thereby reducing the myocardial oxygen demand [1].Myocardial oxygen consumption is relatively high compared to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…17 A study conducted by Teli et al, showed that there was a statistically significant increase in double product in pregnancy in all trimesters and the rise was more noticed in the third trimester. 18 These findings shows that there is an enhanced stroke volume and heart rate during pregnancy which may lead to increased myocardial oxygen demand. Thus, an increase in RPP is an important marker and a risk predictor of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 86%
“…17 A study conducted by Teli et al, showed that there was a statistically significant increase in double product in pregnancy in all trimesters and the rise was more noticed in the third trimester. 18 These findings shows that there is an enhanced stroke volume and heart rate during pregnancy which may lead to increased myocardial oxygen demand. Thus, an increase in RPP is an important marker and a risk predictor of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 86%